The Future of Political Islam and the West: The Islamic Movement in the Arab World with a Focus on Egypt - Hanafi, Hasan (Religious studies and theology, 2013)
Political Islam has taken on new meanings with the revolutions of the Arab Spring, and it is now even more difficult to speak of the West and Islam as opposing forces. This article surveys some of the critical issues associated with the term "Political Islam" and juxtaposes it with the equally difficult term "the West." By way of a case study, it addresses the way in which a distinctive form of Political Islam has gained power in Egypt and attempts to portray the special character imposed on it by Egyptian cultural tradition. The argument ends with a plea to recognize the variety subsumed under the term in any nuanced analysis of Islam today.